2018
DOI: 10.1038/s41390-018-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

Enteric dysbiosis and fecal calprotectin expression in premature infants

Abstract: Background: Premature infants often develop enteric dysbiosis with a preponderance of Gammaproteobacteria, which has been related to adverse clinical outcomes. We investigated the relationship between increasing fecal Gammaproteobacteria and mucosal inflammation, measured by fecal calprotectin (FC). Methods: Stool samples were collected from very-low-birth weight (VLBW) infants at ≤2, 3, and 4 weeks’ postnatal age. Fecal microbiome was surveyed using PCR-amplification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 38 publications
5
32
0
Order By: Relevance
“…Enterobacteriaceae is consistent with examples of preterm infant gut microbiome development in the literature [47,48], with taxa-dependent implications for preterm infant morbidity and development [4,10,45]. Among preterm infants fed EVC001, we observed that novel microbiome compositions developed, where colonization by B. infantis resulted in the displacement of bacteria associated with increased risk of preterm morbidities [5](e.g.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Enterobacteriaceae is consistent with examples of preterm infant gut microbiome development in the literature [47,48], with taxa-dependent implications for preterm infant morbidity and development [4,10,45]. Among preterm infants fed EVC001, we observed that novel microbiome compositions developed, where colonization by B. infantis resulted in the displacement of bacteria associated with increased risk of preterm morbidities [5](e.g.…”
Section: Discussionsupporting
confidence: 83%
“…These services include increased availability of nutrients from human milk, improved maturation of the intestinal epithelium, reduced enteric inflammation, and mitigated risk of infection in hospitalized infants [3,21,43,44,46]. In this study, we found preterm infants in two hospitals were colonized by nosocomially acquired bacteria despite a human milk diet, and the resulting gut microbiomes, absent intervention with B. infantis EVC001, developed comparably to reports in the literature on the preterm infant gut microbiome [1,2,10]. Early acquisition of skin-derived bacteria (e.g.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…inflammation | intestinal | coagulation N ecrotizing enterocolitis (NEC) is an idiopathic, inflammatory bowel necrosis of premature infants and a leading cause of mortality in infants born between 22 and 28 wk of gestation (1)(2)(3). Premature infants who develop bacterial overgrowth and dysbiosis with a predominance of Gram-negative bacteria in their enteric microenvironment may be at enhanced risk of NEC (4)(5)(6). This risk of NEC may increase further upon exposure to environmental insults such as hypoxia and/or hypothermia, inadequate mucosal antimicrobial defenses due to immature Paneth cells, inflammation in the anemic intestine following red-blood-cell transfusions, or following enteral exposure to immunological stimulants (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%